Respuesta :

[tex]\left\{\begin{array}{ccc}3x-9y=6&|divide\ both\ sides\ by\ 3\\2x-11y=6&|divide\ both\ sides\ by\ (-2)\end{array}\right\\\\\underline{+ \left\{\begin{array}{ccc}x-3y=2\\-x+5.5y=-3\end{array}\right}\\.\ \ \ 2.5y=-1[/tex]

Answer:

x=4/5

y=-2/5

Step-by-step explanation:

We have two equations:

[tex]3\cdotx-9\cdoty=6[/tex]

[tex]2\cdotx-11\cdoty=6[/tex]

We can eliminate x by making x of equation 1 be equal to x in the equation 2:

[tex]x=2+3\cdoty[/tex]

Substitute into equation 2:

[tex]2\cdot(2+3\cdoty)-11\cdoty=6[/tex]

Simplify:

[tex]2\cdot2+2\cdot3\cdoty-11\cdoty=6[/tex]

[tex]4+6\cdoty-11\cdoty=6[/tex]

[tex]-5\cdoty=2[/tex]

[tex]y=-2/5[/tex]

Substitute back into one of the equations:

[tex]x=2+3\cdot(-2/5)[/tex]

[tex]x=2-6/5[/tex]

[tex]x=10/5-6/5=4/5[/tex]